Digital infarct and mononeuritis in a middle aged female: always suspect Antineutrophil cytoplasmic antibodies associated vasculitis - Majumdar, Avirup; Atam, Virendra; Pandey, Saurabh; Singh, Prashant; Chauhan, Himanshu (International Journal of Advances in Medicine, 2020)
Vasculitis is a process caused by inflammation of blood vessel walls and results in a variety of disorders. Small-vessel vasculitis (vasculitis involving arteries, venules and capillaries) should be suspected in any patient who presents with a multisystem disease that is not caused by an infectious or malignant process. Testing for Antineutrophil cytoplasmic antibody (ANCA) is the basis of classification of small vessel vasculitis into ANCA associated and non - ANCA associated vasculitis. Apart from cutaneous manifestations like palpable purpura and vasculitic urticaria, digital gangrene in a patient with evidence of mononeuritis multiplex is highly suggestive of ANCA associated vasculitis (AAV). Clinically most of these vasculitides have overlapping clinical presentations and similar treatment. Early diagnosis and rapid initiation of treatment of AAV is recommended rather than ordering for definitive tests (e.g. histopathology or angiograms) since delay in treatment can result in serious end organ damage (pulmonary or renal).